Clinical and Refractive Outcomes of Toric Phakic Implantable Collamer lens Implantat for correction of myopic astigmatism - Amana, Suzan (AL-Kindy College Medical Journal, 2019)
Background: Currently there are four general approaches to correct refractive errors: refractive corneal surgery, crystalline lens surgery and implantation of an intraocular lens in anterior or posterior chamber.Objective: To evaluate the predictability, safety and stability of toric phakic implantable collamer lens implantation to correct moderate to high myopic astigmatism. in  Eye Specialty Private Hospital, Baghdad, Iraq.Type of the Study: a prospective non randomize intervention study.Methods: 60 eyes of 40 patients underwent implantation of a toric implantable collamer lens (V4c design).Mean spherical refraction was ₋11.32 diopter (D) ±3.17 (SD) with range from ₋6.00 to ₋18.00D and the mean cylinder was -2.61(D) ±1.16 with range from ₋1.00 to ₋5.50D .The outcome measures that evaluated during a 12 months follow-up period include UDVA, refractive outcomes, CDVA, vault and adverse events.Results: At 12 months postoperatively the mean Snellen decimal UDVA was 0.77±0.23 and mean CDVA was 0.80±0.21, with an efficacy index 1.16. Twenty nine  eyes (48.33%) showed gain in CDVA with safety index  1.21.The treatment was highly predictable for spherical equivalent and astigmatic component .The mean SE dropped from (₋12.63D ±3.11) to ( ₋0.11 D±0.20) with 58 eyes within ±0.50 D and 60 eyes with ± 1.00D of target correction . For achieved cylinder 60 eyes (100%) had ≤0.50D and 51 eyes (85%) had ≤0.25D with strong positive linear correlation between achieved and expected cylinder(r=0.94)Conclusions: The results of the present study support safety, efficacy, predictability of toric implantable collamer lens implantation to treat moderate to high myopic astigmatism.